Statistical analysis concerning model of quasi-stationary mode of natural gas transportation through pipeline section - Тевяшев, Андрей Дмитриевич; Асаенко, Юрий Сергеевич (Technology audit and production reserves, 2014)
The methods of simulation and statistical linearization are compared in the paper. The main objective of the research lies in determining the most effective method of implementing a stochastic model of a linear pipeline section, for ensuring high performance and accuracy in processing large amounts of information. Modern equipment provides a large amount of data that enables simulating a linear section of a pipeline in real time, possibly, using the suggested methods. The problem of comparing these methods is solved by applying them to a linear section model with specified statistics. As a result, it allows comparing accuracy of the results obtained with these methods. Both methods have advantages and disadvantages and can be used for various purposes. The results of the research are to improve the quality of gas transportation using the most accurate and efficient methods for data processing, in particular.